CTCF functions as an insulator for somatic genes and a chromatin remodeler for pluripotency genes during reprogramming - Song, Yawei; Liang, Zhengyu; Zhang, Jie; Hu, Gongcheng; Wang, Juehan; Li, Yaoyi; Guo, Rong; Dong, Xiaotao; Babarinde, Isaac A.; Ping, Wangfang; Sheng, Ying-Liang; Li, Huanhuan; et al. (Cell reports (Cambridge), 2022)
CTCF mediates chromatin insulation and long-distance enhancer-promoter (EP) interactions; however, little is known about how these regulatory functions are partitioned among target genes in key biological processes. Here, we show that Ctcf expression is progressively increased during induced pluripotency. In this process, CTCF first functions as a chromatin insulator responsible for direct silencing of the somatic gene expression program and, interestingly, elevated Ctcf expression next ensures chromatin accessibility and contributes to increased EP interactions for a fraction of pluripotency-associated genes. Therefore, CTCF functions in a context-specific manner to modulate the 3D genome to enable cellular reprogramming. We further discover that these context-specific CTCF functions also enlist SMARCA5, an imitation switch (ISWI) chromatin remodeler, together rewiring the epigenome to facilitate cell-fate switch. These findings reveal the dual functions of CTCF in conjunction with a key chromatin remodeler to drive reprogramming toward pluripotency. [Display omitted] •Overexpression of Ctcf improves reprogramming to induced pluripotency•CTCF acts as a chromatin insulator to suppress key somatic genes•CTCF also functions as a structural regulator for a subset of pluripotency genes•CTCF maintains chromatin accessibility for pluripotency genes along with SMARCA5 Song et al. show that CTCF modulates the 3D genome to enable cellular reprogramming by acting as an insulator for the somatic program and as an accessible chromatin and structural regulator for pluripotency genes.